An Overview of Research Trend on Merit System in Indonesia and International Practices: A Bibliometric Analysis and Visualization - Rahmah, Mutia; Hamdi, Muchlis (Research and Development Agency Ministry of Home Affairs, 2022)
This study intends to examine how the development of research related to the merit system in Indonesia and international practices. Bibliometric analysis is used to determine the dynamics of the research topics discussed related to the merit system through keywords that appear in the Scopus database until January 7, 2022. Visualization from bibliometric based on co-authorship, co-occurrence, and citation using VOSviewer 1.6.16. This study showed 485 articles had been filtered through the criteria of Open Access, Article, English, and Journal. Six of the 485 articles discussed various aspects of the merit system in Indonesia. In Co-authorship, there are eight of 23 clusters written by more than two people collaborating; the United Kingdom is the highest number of articles published, while Indonesia also appears in the visualization but does not collaborate with affiliated authors from other countries. In co-occurrence, 22 clusters of 1,503 keywords emerge, and 234 meet the threshold. The meritocracy item has the highest link and total link strength, but this item was published on average around the year 2018. In terms of citation, eight of the ten most-cited documents were published more than the last ten years, while the other two documents were published in the last eight years. The document of Pratto f. 1994 was the highest citation document and became an important article related to the merit system discussing social dominance orientation which looks at inequality in social groups.